Genotype by environment (G x E) interaction in cassava (Manihot esculenta Crantz) in Uganda - Ntawuruhunga, Pheneas; Whyte, J.; Dixon, A.; Rubaihayo, P.R. (2009)
Genotype (G) by environment (E) interaction (GEI) in cassava was studied using 10 genotypes in a multilocational trial in Uganda at different altitudes for 2 years. The study investigated the magnitude of GEI and diagnosed the underlying causal factors of the G × E pattern. The analysis of variance indicated that the effects of E, G, and GEI were significant for storage root number, storage root size, storage root girth, fresh storage root weight, and dry yield, but not for dry matter content. Additive Main Effects and Multiplicative Interactions (AMMI) was used to assist the selection and zonation of the environments into homogenous ecosystems. Genotype TMS I 92/0057 was found to have broad adaptation, high yield, and stability, with temperature being one of the underlying causal factors of the interaction. Namulonge (mid-altitude) was identified as a stable environment and could be considered as a site for broad selection.